Níveis de arginina e lisina digestíveis em dietas para codornas japonesas em postura - Mauricio, Thamirys Vianelli (2015)
In order to evaluate different levels of arginine and lysine in diets for Japanese quails and analyze the antagonistic effect of these amino acids were used 880 quail with average weight of 180g at 140 days of age. Distributed in the experimental units in a randomized design. The study had two runs in the first were used five increasing levels of digestible arginine (1,148; 1,256; 1,364; 1,472; 1,580%) under a fixed level of digestible lysine 1.083%, corresponding to arginine: lysine 1, 06; 1.16; 1.26; 1.36 and 1.46, the second trial was characterized by a factorial arrangement (3x2), composed of three levels of lysine (1.083; 1.183; 1.283%) and two levels of arginine (1,472 and 1,580%). So the first test was composed of five treatments and the second six, both with ten replicates. In the first trial was not verified significant effect (P> 0.05) levels of arginine and lysine the exception of the variable "commercial egg" (OC), where it was found decreasing linear effect (P = 0.009) according to the equation: Y = -3,4444X + 103.1342, r² = 0.94, with the level of arginine observed the 1,148%. In the second trial none of the features in question were affected (P> 0.05) by lysine levels and digestible arginine in the study. It was concluded that the level of digestible arginine which provides the best production rates is 1,148% and better digestible lysine and arginine respect to the parameters analyzed was 1.36: 1.00.